Construction of technology-based and personalized curricula for a more flexible and adaptive education - Ahmad Rahmatika; Emilda Sulasmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Digital transformation in education opens up excellent opportunities to produce larger, flexible, and adaptive learning. Technologies such as artificial intelligence (AI), augmented reality (AR), and blockchain allow a learning process more tailored to students' needs and abilities. This approach provides a relevant and interactive learning experience and supports the implementation of the Independent Curriculum in Indonesia, which prioritizes flexibility and innovation in teaching. This research explores the potential and challenges of a technology-based curriculum. The results show that this technology effectively improves learning outcomes, but obstacles exist, such as limited infrastructure, lack of training for educators, and student data privacy issues. The synergy between the government, educational institutions, and the private sector is needed. Providing adequate infrastructure, continuous teacher training, and supportive policies will be the key to successfully implementing a technology-based curriculum. If used properly, this technology can make education systems more relevant, inclusive, and ready for future needs.